PENINGKATAN HASIL PEMBELAJARAN MATEMATIKA MELALUI PEMANFAATAN PORTAL MATEMATIKA PADA JARINGAN INTERNET DENGAN METODE BRAINSTORMING DI KELAS XII MULTIMEDIA 1 SMK NEGERI 1 BENGKULU SELATAN - Nurfadillahwati Nurfadillahwati (PAKAR Pendidikan, 2015)
The purpose of this study is to (1) determine the effectiveness of mathematics’ learning through the use of mathematical portal in the Internet by brainstorming method to increase students’ learning outcomes in statistical learning materials; (2) determine the effectiveness of Classroom Action Research (CAR) to improve the quality of mathematics’ instruction in the matter of statistics. The results showed that the learning outcomes of mathematics learners constantly increased in each cycle. The learning results of the students monitored from the average value of the class in three meetings in the first cycle were 77.36. The mastery learning percentage reaching up to 78.57% in the classical meaning in this cycle has not been achieved. The result of Cycle II of the students monitored from the average value of the class in three meetings was 79.42. The percentage of learning mastery in the classical meaning (89.29) in this cycle had been reached. The conclusion of this study showed that the application of mathematics learning through the use of mathematical portal in the internet by brainstorming methods in mathematics learning is proven effective in improving the students’ learning outcomes in mathematics.